The impact of exercise intended for fitness or sport on the prevalence of non‐specific neck pain in adults: A systematic review. (29th September 2021) - Ireland, Josh; Window, Peter; O'Leary, Shaun P.
Abstract: Objective: This study systematically reviewed the literature investigating the relationship between participation in exercise intended to improve fitness or sport and the prevalence of non‐specific neck pain in adults. A secondary objective evaluated if exercise characteristics (frequency, and total duration of weekly exercise) impacted any observed relationship between this form of exercise and neck pain prevalence. Design: Narrative systematic review. Literature Search: Six databases including Pubmed/Medline, Scopus, EMBASE, SPORTDiscus, CINAHL, and the Cochrane Library were searched from their inception up to April 2021. Study Selection Criteria: Studies were deemed eligible if they investigated the relationship between exercise participation and prevalence of non‐specific neck pain. Only full‐text, cross‐sectional and longitudinal studies in an adult population were included. Data Synthesis: Due to heterogeneity of characteristics in the included studies, a meta‐analysis was not deemed feasible. Data were synthesised using narrative synthesis with subgroup analysis of exercise themes including frequency, and total weekly duration. Results: Fair to good quality evidence from eight studies indicated that regular participation in exercise intended for fitness or sport was associated with a reduced prevalence of neck pain in adults. Three cross‐sectional studies reported a positive relationship between greater weekly exercise duration and reduced neck pain prevalence. Conclusion: The results of this review provide preliminary evidence of a potential protective effect of participation in exercise intended for fitness or sport on the prevalence of non‐specific neck pain in the community. This protective relationship appeared to be stronger when exercise was undertaken for a greater total weekly duration.